Integration of Internet of Things and cloud computing: a systematic survey. Issue 2 (1st January 2020) - Nazari Jahantigh, Motahareh; Masoud Rahmani, Amir; Jafari Navimirour, Nima; Rezaee, Ali
Abstract : There are two different concepts [Internet of Things (IoT) and cloud computing] influencing our lives in many ways as they will further be used and highlighted in the future of the Internet. The present systematic study discusses a combination of these two concepts. Many studies have focused on IoT and cloud computing separately. These studies lack a deep investigation of their combination, which has new challenges and issues. Yet, the recent integration of them has been paid a primary focus. This systematic study attempts to analyse how the combination of IoT and cloud has been presented and detects the challenges and metrics of such integration. Further, this analysis aims to develop an understanding of the current affair of this integration by overviewing a collection of 38 recent papers. The contributions of this study, in brief, are: (i) overviewing the current challenges correlated with combination of cloud computing and IoT; (ii) presenting the anatomy of some proposed combination platforms, applications, and integrations; (iii) summarising major areas to boost the integration of cloud and IoT in the upcoming works.